PENERAPAN INTEGRATED MARKETING COMMUNICATION GALERI WIRDA PONDOK UNGU BEKASI - Sulaeman, Dede; Novia, Reni; Vanny, Amanda Sherly Devita (DIALEKTIKA KOMUNIKA: Jurnal Kajian Komunikasi dan Pembangunan Daerah, 2024)
Micro, Small, and Medium Enterprises (MSMEs) are the most common type of business, especially in Indonesia. Many business sectors are the same, so there are many competitors. The clothing store Galeri Wirda Pondok Ungu Bekasi, as an MSME in the clothing sector, for example, with many of the same and similar businesses, requires a marketing strategy. The role of Integrated Marketing Communication (IMC) as a marketing strategy in providing clear information to consumers with various marketing media helps businesses survive and increase their sales. By using the analysis of IMC theory, this study aims to determine the role of IMC as a marketing strategy for a business. This study uses qualitative methods with a post positivism paradigm, collecting data using observation techniques, literature studies, documentation, and in-depth interviews. The research results show that the application of Integrated Marketing Communication helps business actors develop their businesses. Keywords: Micro, Small, and Medium Enterprises, Marketing Communications, Integrated Marketing Communication, Consumers, Clothes